Fungal Infection - Silva de Loreto, Érico; Simoni Moraes Tondolo, Juliana (IntechOpen, 2019)
This book aims to provide readers with some of the current trends in mycology. Its chapters include discussions on the major invasive fungal diseases, host-pathogen interactions, relationships between fungal growth and the environment, the use of fungal species to control soil parasites, and the antifungal properties of thiosulfonates. The information herein covers topics in mycological research and will be of interest to students and researchers in all biological sciences.